Effects of 4-Hydroxy-2, 3, 3′, 4′, 5-Pentachlorobiphenyl (4-OH-CB107) on Liver Transcriptome in Rats: Implication in the Disruption of Circadian Rhythm and Fatty Acid Metabolism. (21st May 2018) - Ochiai, Mari; Iida, Midori; Agusa, Tetsuro; Takaguchi, Kohki; Fujii, Satoshi; Nomiyama, Kei; Iwata, Hisato
Abstract: Polychlorinated biphenyls (PCBs) and their hydroxylated metabolites (OH-PCBs) have been detected in tissues of both wild animals and humans. Several previous studies have suggested adverse effects of OH-PCBs on the endocrine and nervous systems in mammals. However, there have been no studies on transcriptome analysis of the effects of OH-PCBs, and thus, the whole picture and mechanisms underlying the adverse effects induced by OH-PCBs are still poorly understood. We therefore investigated the mRNA expression profile in the liver of adult male Wistar rats treated with 4-hydroxy-2, 3, 3′, 4′, 5-pentachlorobiphenyl (4-OH-CB107) to explore the genes responsive to OH-PCBs and to understand the potential effects of the chemical. Next-generation RNA sequencing analysis revealed changes in the expression of genes involved in the circadian rhythm and fatty acid metabolism, such as nuclear receptor subfamily 1, group D, member 1, aryl hydrocarbon receptor nuclear translocator-like protein 1, cryptochrome circadian clock 1, and enoyl-CoA hydratase and 3-hydroxyacyl-CoA dehydrogenase, in 4-OH-CB107-treated rats. In addition, biochemical analysis of the plasma revealed a dose-dependent increase in the leucine aminopeptidase, indicating the onset of liver damage. These results suggest that OH-PCB exposure may induce liver injury as well as disrupt the circadian rhythm and peroxisome proliferator-activated receptor-related fatty acid metabolism.